Anaesthesia and the Acute Phase Protein Response in Children Undergoing Circumcision - Unase Buyukkocak; Fatma Caglayan; Osman Caglayan; Murat Basar; Murat Cakmak; Ertan Batislam; Sevgi Ulusoy (Hindawi Limited, 2005)
Concentrations of acute phase proteins (CRP: C-reactive protein, albumin) change during surgery. We investigated the acute phase response to circumcision and the effects of anaesthesia on this response. The children were divided into four groups; group 1 (intratracheal general anaesthesia, n=40), group 2 (general anaesthesia with mask, n=20), group 3 (ketamine, n=20), group 4 (local anaesthesia, n=35). Blood samples were obtained, 24 hours before circumcision, after premedication, and 24 hours after circumcision. CRP and albumin before circumcision were comparable for all groups. There was no increase in CRP, and albumin remained steady throughout the study. No difference was observed among the groups, and related to anaesthesia. No responsiveness may be explained with the size of injured tissue or anatomical and histological type of preputium.